Field Emission Electron Source Based on Silicon Carbide Nanopillars - Yeşilpınar, Damla; Demir, Mustafa Muammer; Çelebi, Cem (Izmir Institute of Technology, 2017)
In this thesis work, I studied the fabrication and the field emission characteristics of SiC nanopillar based electron field emitters. The first objective of this thesis was to fabricate a large area nanopillar array on bulk 6H-SiC substrate. Accordingly, a nanosphere assisted technique was developed to create a conventional Cr/Ni hard mask to acquire desired etch mask pattern on the C-terminated face of 6H-SiC. The nanopillars were then fabricated by ICP-RIE. Two sets of nanopillars with different aspect ratios and geometries were fabricated for two different ICP-RIE durations. 1 min long etch resulted in nanopillar arrays with blunt tip apex and an aspect ratio of 3.4, where 2 min long etch produced nanopillar arrays with an aspect ratio of 4.9 and a sharp tip apex with an estimated radius of curvature of about 18 nm. As the second objective; the electron field emission characteristics of the produced nanopillars with two different aspect ratios and geometries were investigated and the obtained results were compared with each other. We found that the nanopillars with sharp tip apex produced field emission currents up to 240 μA/cm2 under 17.4 V/μm applied electric field, as the nanopillars with blunt tip apex produced an emission current of 70 μA/cm2. The threshold electric fields were found to be 9.1 V/μm and 7.2 V/μm for the nanopillars with blunt and sharp tip apex, respectively. Time dependent stability measurements yielded stable electron emission without any abrupt change in the respective current levels of both samples.

Bu tez çalışmasında Silisyum Karbür nanosütun bazlı elektron alan emisyon kaynağının fabrikasyonu ve alan emisyon karakteristiklerini inceledim. Bu tezin ilk amacı, 6H-SiC alttaşının üzerinde geniş alan nanosütun dizilerinin oluşturulmasıydı. Bu nedenle, nanoküre litografisine dayanan bir teknik geliştirilerek konvansiyonel Cr/Ni sert aşındırma maskesinin istenen dizilimde 6H-SiC alttaşın C-termine yüzünde oluşturulması sağlandı. Daha sonra nanosütunlar ICP-RIE işlemi ile üretildi. Farklı boy-en oranına ve uç şekillerine sahip olan iki set örnek, farklı sürelerde ICP-RIE uygulanarak elde edildi. 1 dakika boyunca aşındırılan örnekte nanosütunların boy-en oranının 3.4 olduğu ve düz bir uç noktasına sahip olduğu görüldü. 2 dakika boyunca aşındırılan örnekte nanosütunların yaklaşık 18 nm eğrilik yarıçapına sahip ve keskin uca sahip olduğu, boy-en oranlarının ise 4.9 olduğu görüldü. İkinci amaç olarak, elde edilen farklı boy-en oranına ve geometriye sahip iki set nanosütunun elektron alan emisyon karakteristikleri incelendi ve elde edilen sonuçlar birbirileri ile karşılaştırıldı. Keskin uca sahip nanosütunların 17.4 V/μm elektrik alan altında 240 μA/cm2 akıma ulaştığı, düz uca sahip nanosütunların ise bu elektrik alan değerinde 70 μA/cm2 akım ürettiği görüldü. Eşik elektrik alan değerleri düz uca sahip örnek için 9.1 V/μm, keskin uca sahip örnek için 7.2 V/μm olarak bulundu. Zamana bağlı durağanlık ölçümleri kararlı bir alan emisyon akımı elde edildiğini gösterdi; alan emisyon akımınlarında ani bir değişim gözlenmedi.
Silisyum Karbür Nanosütun Bazlı Alan Emisyon Elektron Kaynağı
Thesis (Master)--Izmir Institute of Technology, Materials Science and Engineering, Izmir, 2017
Includes bibliographical references (leaves: 70-81)
Text in English; Abstract: Turkish and English
Keywords: Silicon carbide; Nanopillars; Electron sources; Field emission